2021
DOI: 10.1021/acsnano.1c00251
|View full text |Cite
|
Sign up to set email alerts
|

Tuning the Spin Density of Cobalt Single-Atom Catalysts for Efficient Oxygen Evolution

Abstract: Single-atom catalysts (SACs) with magnetic elements as the active center have been widely exploited for efficient electrochemical conversions. Understanding the catalytic role of spin, and thus modulating the spin density of a single-atom center, is of profound fundamental interest and technological impact. Here, we synthesized ferromagnetic single Co atom catalysts on TaS2 monolayers (Co1/TaS2) as a model system to explore the spin–activity correlation for the oxygen evolution reaction (OER). A single Co atom… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
93
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 139 publications
(97 citation statements)
references
References 50 publications
4
93
0
Order By: Relevance
“… 103 The spin–activity correlation in a single Co atom supported by TaS 2 -catalyzed oxygen evolution reaction was also reported in a combined experimental and theoretical work. 104 By using ab initio nonadiabatic molecular dynamics simulations, Cheng et al found the spin selection could enhance charge carrier lifetimes and thus boost the reaction in a photocatalytic water-splitting reaction catalyzed by single copper atoms on Anatase TiO 2 . 105 Both experiments and simulations have demonstrated that the rational modulating spin states of SACs is a promising method to boost the catalytic performance.…”
Section: New Conceptsmentioning
confidence: 99%
See 1 more Smart Citation
“… 103 The spin–activity correlation in a single Co atom supported by TaS 2 -catalyzed oxygen evolution reaction was also reported in a combined experimental and theoretical work. 104 By using ab initio nonadiabatic molecular dynamics simulations, Cheng et al found the spin selection could enhance charge carrier lifetimes and thus boost the reaction in a photocatalytic water-splitting reaction catalyzed by single copper atoms on Anatase TiO 2 . 105 Both experiments and simulations have demonstrated that the rational modulating spin states of SACs is a promising method to boost the catalytic performance.…”
Section: New Conceptsmentioning
confidence: 99%
“…Very recently, Gong et al successfully fabricated the single Co atoms centered in porphyrin units of covalent organic frameworks (COFs), COF-367-Co. 102 They found that by rationally regulating the oxidation states of single Co atoms such as Co II -TAP and Co III -TAP, as shown in Figure 7a 103 The spin−activity correlation in a single Co atom supported by TaS 2 -catalyzed oxygen evolution reaction was also reported in a combined experimental and theoretical work. 104 By using ab initio nonadiabatic molecular dynamics simulations, Cheng et al found the spin selection could enhance charge carrier lifetimes and thus boost the reaction in a photocatalytic water-splitting reaction catalyzed by single copper atoms on Anatase TiO 2 . 105 Both experiments and simulations have demonstrated that the rational modulating spin states of SACs is a promising method to boost the catalytic performance.…”
Section: Magnetic Single-atom Catalystmentioning
confidence: 99%
“…[15][16][17] More recently, a great deal of effort has been made to develop single-atom electrocatalysts (SACs) with excellent atom-utilization efficiency to address the abovementioned issues and accelerate water electrolysis. [18][19][20] However, SACs face several of their own drawbacks such as low volume of production, the complex equipment, and extremely controlled conditions required, ambiguous number of active site as well as their high cost which unfavorable to use it in large scale. [21] Besides these catalysts, metal-free nitrogenous carbon catalysts have received enormous interest and have already shown their potential to be used as the replacement for expensive metallic catalysts in FCs and water splitting cells [22][23][24][25] due to their low cost, huge surface area, desirable chemical stability, high electrical conductivity, remarkable resistance to CO poisoning, and multifunctionality.…”
Section: Hollow Carbon Nanoballs On Graphene As Metal-free Catalyst For Overall Electrochemical Water Splittingmentioning
confidence: 99%
“…), 8–13 SACs contribute an excellent platform to explore great potential catalysts for different catalytic reactions, e.g. , water splitting, 14–16 nitrogen reduction reaction (NRR) 17–20 and carbon dioxide reduction reaction (CO 2 RR). 21–24 In these SACs, nitrogen (N) atoms are the common ligands used to anchor transition metal centers (TM); thus, the N-coordination environment (denoted as N x , where x is the N-coordination number) is of great importance to determine the catalytic performance of TM SACs.…”
Section: Introductionmentioning
confidence: 99%